Entrepreneurship and personal income tax: evidence from Canadian provinces - Ferede, Ergete (My University, 2019)
This paper employs the dynamic panel estimation method to investigate the effects of the top personal income tax rate on entrepreneurship as proxied by the employer business entry rate using data from Canadian provinces over the period 1984–2015. The empirical findings of this paper show that the top income tax rate has a negative and statistically significant effect on entrepreneurship both in the short and long term. According to the preferred estimate of this study, a one percentage point increase in the top statutory marginal income tax rate is associated with a 0.13 percentage point decrease in the business entry rate in the short term and a 0.41 percentage point decrease in the long term. Based on the long-term results, on average, a province that raises its top personal income tax rate by one percentage point can expect to have about 405 fewer new employer businesses enter its economy. This is a significant loss for an economy that has been experiencing a decline in entrepreneurship for a long time. The key findings of this paper are robust to various sensitivity checks.
Keywords: entrepreneurship; income tax; occupational choice; start-ups